2017
DOI: 10.3389/fcimb.2017.00465
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus equi subsp. zooepidemicus Invades and Survives in Epithelial Cells

Abstract: Streptococcus equi subsp. zooepidemicus (S. zooepidemicus) is an opportunistic pathogen of several species including humans. S. zooepidemicus is found on mucus membranes of healthy horses, but can cause acute and chronic endometritis. Recently S. zooepidemicus was found able to reside in the endometrium for prolonged periods of time. Thus, we hypothesized that an intracellular phase may be part of the S. zooepidemicus pathogenesis and investigated if S. zooepidemicus was able to invade and survive inside epith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 62 publications
(86 reference statements)
0
15
0
1
Order By: Relevance
“…Staphylococcus spp pueden producir, además, neumonía y mastitis purulenta, así como conjuntivitis ( Dentro del mecanismo de infección de S. zooepidemicus, se sabe que la mucosa oral intacta podría ser la vía de entrada directa, favorecida por la abrasión o lesión pro-ducto de mordeduras en piel o mediante aerosoles (Murphy et al, 1991;Percy y Barthold, 2007). Recientemente se ha sugerido que dicho agente tendría una fase intracelular, lo cual podría favorecer la sobrevivencia en el hospedero y explicaría en parte las infecciones recurrentes o persistentes (Skive et al, 2017). A pesar de que los ganglios linfáticos cervicales son un lugar común de infección bacteriana y, por tanto, de formación de abscesos, otros ganglios u órganos puedes verse comprometidos (Harkness y Wagner, 1995).…”
Section: Discussionunclassified
“…Staphylococcus spp pueden producir, además, neumonía y mastitis purulenta, así como conjuntivitis ( Dentro del mecanismo de infección de S. zooepidemicus, se sabe que la mucosa oral intacta podría ser la vía de entrada directa, favorecida por la abrasión o lesión pro-ducto de mordeduras en piel o mediante aerosoles (Murphy et al, 1991;Percy y Barthold, 2007). Recientemente se ha sugerido que dicho agente tendría una fase intracelular, lo cual podría favorecer la sobrevivencia en el hospedero y explicaría en parte las infecciones recurrentes o persistentes (Skive et al, 2017). A pesar de que los ganglios linfáticos cervicales son un lugar común de infección bacteriana y, por tanto, de formación de abscesos, otros ganglios u órganos puedes verse comprometidos (Harkness y Wagner, 1995).…”
Section: Discussionunclassified
“…In vitro experiments have demonstrated the ability of S. zooepidemicus to survive within epithelial cells, which could contribute to the persistent and recurrent infection described in horses. 28 In addition, S. zooepidemicus isolates with increased capsular production have been linked with enhancement of antiphagocytic ability in experimentally infected mice and are often obtained from horses with opportunistic respiratory tract infection. 3,12 Interestingly, instability of capsular expression has been reported on primary culture of S. zooepidemicus in contrast to the robust capsular production in the closely related S. equi subsp.…”
mentioning
confidence: 99%
“…This microorganism caused an epidemic of respiratory diseases among several thousand Icelandic horses in 2010 [68,83,88]. Skive et al [89] demonstrated the viability of SEZ in the endometrium, suggesting its intracellular viability.…”
Section: Streptococcus Equi Subsp Zooepidemicus (Sez)mentioning
confidence: 99%
“…Skive et al . [89] demonstrated the viability of SEZ in the endometrium, suggesting its intracellular viability.…”
Section: Introductionmentioning
confidence: 99%